2020
DOI: 10.1073/pnas.1821367117
|View full text |Cite
|
Sign up to set email alerts
|

Population-based RNA profiling in Add Health finds social disparities in inflammatory and antiviral gene regulation to emerge by young adulthood

Abstract: SOCIAL SCIENCES MEDICAL SCIENCES Note: Descriptive statistics are weighted; 43 in analytic sample are missing sample 1 weights. *Two-tailed single-sample t test: RNA sample mean = Wave V sample 1 mean. † Two-sided binomial test: RNA sample proportion = Wave V sample 1 proportion. ‡ χ 2 test: RNA sample proportions = Wave V sample 1 proportions. Cole et al. PNAS | March 3, 2020 | vol. 117 | no. 9 | 4603 SOCIAL SCIENCES MEDICAL SCIENCES

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 72 publications
2
70
0
Order By: Relevance
“…This cohort study of normal young adults demonstrated increased upregulation of interferon gene expression in Blacks and Asians relative to non-Hispanic whites. 39 We observed upregulation of interferon-responsive complement genes at onset of TA-TMA that returned to baseline after resolution of TA-TMA. These novel findings are in agreement with the highly inflammatory clinical phenotype of children presenting with severe TA-TMA, and may explain, at least in part, incomplete response to complement blocking therapy in some patients, especially after allogeneic transplant, despite achievement of therapeutic drug concentration in the blood.…”
Section: Discussionmentioning
confidence: 67%
“…This cohort study of normal young adults demonstrated increased upregulation of interferon gene expression in Blacks and Asians relative to non-Hispanic whites. 39 We observed upregulation of interferon-responsive complement genes at onset of TA-TMA that returned to baseline after resolution of TA-TMA. These novel findings are in agreement with the highly inflammatory clinical phenotype of children presenting with severe TA-TMA, and may explain, at least in part, incomplete response to complement blocking therapy in some patients, especially after allogeneic transplant, despite achievement of therapeutic drug concentration in the blood.…”
Section: Discussionmentioning
confidence: 67%
“…Major immunological mechanisms in COVID-19 include: 19,20 This observation goes hand in hand with prevalence of lupus in these ethnicities, a predominantly type 1 IFN-driven disease.…”
Section: Ba S Ic Immune Inj Urie S In Covid -19 -A De Ja V U Of Lupmentioning
confidence: 99%
“…Body mass index (BMI) and smoking also increases type I IFN expression and inflammatory cytokines. 20 These 2 risk factors tend to adversely affect outcome of COVID-19 disease as well as lupus and other systemic autoimmune diseases. [21][22][23] These reports suggest that gender, ethnicity, BMI and smoking affect type I IFN secretion.…”
Section: F I G U R E 1 Comparison Of Demographic and Clinical Charactmentioning
confidence: 99%
“…The CRTA is a stress response pathway mediated by the sympathetic nervous system and beta-adrenergic signaling to induce transcriptional activation of inflammatory genes in the immune system [31,34]. In a recent study of over 1,000 diverse and young adults, family poverty status was associated with transcription of interferon-response factors and immune cell activation of dendritic cells and may contribute to lifespan-related predisposition to inflammatory diseases and conditions [35].…”
Section: Introductionmentioning
confidence: 99%